Hydroxyapatite-filled osteoinductive and piezoelectric nanofibers for bone tissue engineering - Frederico Barbosa; Fábio F. F. Garrudo; Paola S. Alberte; Leonor Resina; Marta S. Carvalho; Akhil Jain; Ana C. Marques; Francesc Estrany; Frankie J. Rawson; Carlos Aléman; Frederico Castelo Ferreira; João C. Silva (Science and Technology of Advanced Materials)
Osteoporotic-related fractures are among the leading causes of chronic disease morbidity in Europe and in the US. While a significant percentage of fractures can be repaired naturally, in delayed-union and non-union fractures surgical intervention is necessary for proper bone regeneration. Given the current lack of optimized clinical techniques to adequately address this issue, bone tissue engineering (BTE) strategies focusing on the development of scaffolds for temporarily replacing damaged bone and supporting its regeneration process have been gaining interest. The piezoelectric properties of bone, which have an important role in tissue homeostasis and regeneration, have been frequently neglected in the design of BTE scaffolds. Therefore, in this study, we developed novel hydroxyapatite (HAp)-filled osteoinductive and piezoelectric poly(vinylidene fluoride-co-tetrafluoroethylene) (PVDF-TrFE) nanofibers via electrospinning capable of replicating the tissue’s fibrous extracellular matrix (ECM) composition and native piezoelectric properties. The developed PVDF-TrFE/HAp nanofibers had biomimetic collagen fibril-like diameters, as well as enhanced piezoelectric and surface properties, which translated into a better capacity to assist the mineralization process and cell proliferation. The biological cues provided by the HAp nanoparticles enhanced the osteogenic differentiation of seeded human mesenchymal stem/stromal cells (MSCs) as observed by the increased ALP activity, cell-secreted calcium deposition and osteogenic gene expression levels observed for the HAp-containing fibers. Overall, our findings describe the potential of combining PVDF-TrFE and HAp for developing electroactive and osteoinductive nanofibers capable of supporting bone tissue regeneration.